Retailer's product line choice with manufacturer's multichannel marketing - Cong Pan (Osaka University, Institute of Social and Economic Research (ISER), 2016)
This paper studies how a retailer decides the length of product line in a vertically related industry. We study a market with two product varieties. Each retailer decides the number of varieties it procures from an upstream manufacturer. The manufacturer may open an online store and encroach on the resale market. In the case of a monopoly retailer, anticipating the online store's encroachment, the retailer may be willing to shorten its product line, although it can choose a full-length one. In the case of duopoly retailers, on the other hand, retailers may make their product lines completely overlapped, partially overlapped, or non-overlapped. Moreover, the total surplus may decrease due to the efficiency loss in the online channel, although the competition in the resale market becomes more intense.
Keywords: L14; L22; M11; 330; channels of distribution; encroachment; buyer power; product line choice